THE ROLE AND SIGNIFICANCE OF FOLKLORE IN THE UPBRINGING OF PRIMARY SCHOOL-AGE STUDENTS - Qadirov, Jurabek Ayitbayevich (SCIENCE and SOCIETY, 2026)
This article examines the pedagogical potential of Uzbek oral folk literature in the moral education of primary school students. It analyzes the role of folklore in developing national values, ethical qualities, patriotism, independent thinking, and speech culture among young learners. The educational significance of fairy tales, proverbs, riddles, and epic works is discussed, and recommendations are provided for integrating folklore into contemporary primary education.